Managing the Post‐acquisition Integration Process: How the Human Iintegration and Task Integration Processes Interact to Foster Value Creation - Birkinshaw, Julian; Bresman, Henrik; Håkanson, Lars (Journal of Management Studies, 2000)
The paper reports a study of the post‐acquisition integration process in three foreign acquisitions made by Swedish multinationals. Detailed interview data and questionnaire responses in both acquiring and acquired firms are presented. The sub‐processes of task integration and human integration are separated out and it is shown that effective integration in these cases was achieved through a two‐phase process. In phase one, task integration led to a satisficing solution that limited the interaction between acquired and acquiring units, while human integration proceeded smoothly and led to cultural convergence and mutual respect. In phase two, there was renewed task integration built on the success of the human integration that had been achieved, which led to much greater interdependencies between acquired and acquiring units.